PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: PERAN MODERASI CORPORATE SOSIAL RESPONSIBILITY - Aslihatin Nisa; Suwandi Suwandi (PROCEEDING UMSURABAYA, 2022)
This study examines the effect of good corporate governance on firm value with corporate social responsibility as a moderating variable. The population used in this study are companies classified in the 2017-2020 LQ45 index. The sample of this study amounted to 180 pieces selected based on the purposive sampling technique. This study uses quantitative methods with secondary data sources in the form of complete annual financial statements of the company. The results of this study indicate that institutional ownership affects firm value. Meanwhile, Managerial Ownership, Independent Commissioner and Audit Committee do not influence Company Value. And for the moderating variable Corporate Responsibility equally cannot moderate the relationship between Managerial Ownership, Ownership, Institutional, Independent Commissioner and Audit Committee on Company Value.Keywords: Managerial ownership; Institutional Ownership; Independent Commissioner; Audit Committee; Corporate social responsibility